Child development and relationships - Flake-Hobson, Carol; Robinson, Bryan E.; Skeen, Patsy (Reading, Mass. : Addison-Wesley Pub. Co, 1983)
Examines the physical and psychological development of children during the stages of infancy, the preschool years, grade school, and adolescence.
Includes bibliography and index.
Keywords: Child development; Interpersonal relations